PENGEMBANGAN MODEL KONSEPTUAL TENTANG KETERKAITAN PARA PELAKU DENGAN KELUASAN PERENCANAAN SUKSESI PADA PERUSAHAAN KELUARGA - Harsono, Mugi (Benefit, 2007)
This seminal article discusses the basic concept of succession planning in family business. Family business succession has been a central subject in fsmily business research since it only has smallsatisfaction number of generation shifts. Succession planning is a long term process, consist of sequential activities to set up and make certain family business sustainability through generation shift. There are two medels of succession management process; first, succession anagement process based on corporation activities held by Aon Consulting Group Forum (2003), and second, succession management process based on treatment to successor proposed by Scarborough &Zimmerer (2006). Succession performers in business family arepredecessors, successors, and siblings. The succession planning activities consist of four categories; successor selection and training, postsuccession business strategy, the role of predesessor at post succession, and the dissemination of succession result informati on to stakeholders.Finally, the conceptual model of succession planning in family business was developed .